Examining Mathematical Communication Ability in Geometric Transformation: An Analysis of Student Test Results - Firza Mufti Aulia; Hasanuddin; Abdur Rahman Hakim (Universitas Islam Lamongan, 2025)
The purpose of this research is to analyze students' mathematical communication ability (MCA) through test questions on geometry transformation material that contains MCA indicators. This research uses a descriptive quantitative approach, by measuring the validity of the questions, then giving test questions to students, calculating student scores, and grouping them by category, and analyzing student answers. The research was conducted at a senior high school in Indragiri Hilir, the research sample was class 12 students majoring in mathematics and science as many as 20 people, with the assessment method and research instruments namely open description questions. The test questions given have been tested for validity using the Aiken index, and are in accordance with the MCA indicators set. The results of the study based on student test scores obtained 20% of high category students, 65% of medium category students, and 15% of low category students in solving MCA test questions. From the results of this study, it is necessary to strengthen learning to facilitate students' MCA.